A new reticulated beetle (Coleoptera: Cupedidae) from Mexico with a catalogue of Cupedidae species of the world - Rodríguez-Mirón, Geovanni M.; López-Pérez, Sara (Zootaxa, 2019)
Paracupes mexicanus sp. nov., from Chiapas, Mexico, is described and illustrated. The subgenus Paracupoides Kirejtshuk et al., 2016 is synonymized under Paracupes Kolbe, 1898. Also, Rhipsideigma is synonymized with Cupes, resulting in new combinations: Cupes adjuncta (Neboiss) and Cupes anosibense (Neboiss), and restored combinations: Cupes cretaceotincta Kolbe, Cupes lugubris Fairmaire and Cupes raffrayi Fairmaire. Also, Cupes leucophaea Newman is reinstated from synonymy of Tenomerga leucophaea. In addition, a catalogue of the Cupedidae species of the world is presented.